2016
DOI: 10.5536/kjps.2016.43.4.253
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hen Age on Egg Quality in Commercial Layer

Abstract: Egg quality is a very important factor for both consumers and producers. Factors affecting egg quality include strain and age of hens; egg storage temperature, time, and humidity; laying season; and feeding. This study aimed to determine the effect of hen age and egg storage time on egg quality. A total of 700 eggs obtained from Hyline Brown commercial layers were used for this experiment, and they were separated into two hen age groups (30 vs. 60 weeks) with eight treatments and four storage times (day 0, 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
7
10
2
Order By: Relevance
“…Authors such as Tůmová et al (2007) or Hanusová et al (2015) confirm the significant effect of genotype on eggshell thickness. According to Lee et al (2016) the effect of age on eggshell thickness is statistically significant, which contradicts our results. Furthermore, findings from Lee et al (2016) show decreasing trend of eggshell thickness with the age.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Authors such as Tůmová et al (2007) or Hanusová et al (2015) confirm the significant effect of genotype on eggshell thickness. According to Lee et al (2016) the effect of age on eggshell thickness is statistically significant, which contradicts our results. Furthermore, findings from Lee et al (2016) show decreasing trend of eggshell thickness with the age.…”
Section: Discussioncontrasting
confidence: 99%
“…According to Lee et al (2016) the effect of age on eggshell thickness is statistically significant, which contradicts our results. Furthermore, findings from Lee et al (2016) show decreasing trend of eggshell thickness with the age. Zita et al (2009) found the significant interaction between age and genotype in eggshell thickness, whereas Petričević et al (2017) claim the opposite.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, egg weight increased significantly from week 25 to week 30, at 60 g and 63 g, respectively ( p < 0.001), and this increase may be due to an increase in hen age, as similarly reported by Lacin et al [ 4 ]. The egg weight recorded at 30 weeks in this study was similar to the results of Lee et al [ 17 ], who reported an average egg weight of 64.1 g ± 3.6 for the HyLine Brown breed of hens at 30 weeks of age. Conversely, the average eggs from the current study were heavier, 61 g, when compared to the work of Roberts et al [ 18 ], who recorded an average egg weight of 57.6 g in their study with ISA Brown hens aged between 25 and 40 weeks old.…”
Section: Discussionsupporting
confidence: 90%
“…Among these factors, hen age is one of the main components affecting eggshell quality. Many researchers have reported that eggshell thickness decreased with increasing hen age ( Lee et al, 2016a ; Molnár et al, 2016 ; Rodríguez-Navarro et al, 2002 ). This was considered to be the most important factor in reducing eggshell quality.…”
Section: Discussionmentioning
confidence: 99%